The Thermal Background to Metamorphism -1. Simple One-Dimensional Conductive Models - Nisbet, E.; Fowler, C. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1982)
Summary Simple conductive geotherm calculations provide a useful way of illustrating the thermal constraints on metamorphism in teaching senior undergraduate classes. In this article a variety of one-dimensional problems is examined to show the effects of variation in conductivity, heat production and mantle contribution, and also to show the time needed for a rock column to reequilibrate thermally after erosion.